1991
DOI: 10.1002/gcc.2870030508
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Changes in the IL‐I (2F) Chromosomal Region of Some Radiation‐Induced Acute Myeloid Leukaemias Carrying Chromosome 2 Rearrangements

Abstract: Acute myeloid leukaemias (AML) arising in irradiated CBA/H mice frequently have breakpoints in the F region of chromosome 2. The closely linked cytokine genes interleukin (IL)-1 alpha and beta map to this region, and the beta gene is deregulated in some AMLs. Using pulsed-field gel electrophoresis techniques, we show here that an 800 kb 2F region encoding IL-1 alpha and beta is not obviously rearranged in six leukaemias carrying chromosome 2 abnormalities. However, changes in IL-1 region DNA methylation in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…These were diagnosed on the basis of established histopathological criteria and studied either at the primary stage or at the in vivo passages given elsewhere (7). DNA Preparation, Digestion, and Analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These were diagnosed on the basis of established histopathological criteria and studied either at the primary stage or at the in vivo passages given elsewhere (7). DNA Preparation, Digestion, and Analysis.…”
Section: Methodsmentioning
confidence: 99%
“…DNA fragments were transferred to Hybond N+ membranes (Amersham) using 0.4 M NaOH and hybridized overnight at 480C with a (TTAGGG)4 synthetic oligonucleotide prepared and labeled as described elsewhere (11). Conditions for membrane hybridization and washing were the same as those described (7). Membranes were subsequently autoradiographed overnight using intensifying screens (Kodak The publication costs of this article were defrayed in part by page charge payment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclei were counted and approximately 1×10 6 were embedded in 1% low gelling temperature agarose (Flowgen). Agarose plugs were then processed according to Anand (1986) and the DNA in plugs digested with 80 U Hinf1 for 4 h at 37°C, as described previously (Silver et al, 1991). DNA was fractionated though a 1% agarose gel in 0.5 × Trisborate-EDTA buffer by pulsed field gel electrophoresis (PFGE) using a CHEF mapper system (Biorad).…”
Section: Telomere Length Analysismentioning
confidence: 99%
“…These data provide strong evidence indicating that imprinting may play an important role in the acquired chromosomal rearrangement and add a new dimension to the whole field of human hemopoietically derived cancers; in most of them, somatic chromosomal rearrangements are involved. It has been reported that a similar mechanism operates in certain murine leukemias (Silva et al, 1991), and it has been proposed that translocation of a n imprinted gene to a new location may activate these genes Reik, 1992). We suggest that imprinted genes play a special role in carcinogenesis through two independent mechanisms: 1) a n imprinted gene may act as a tumor suppressor gene and imprinting inactivates one of the gene's allele; 2) they act through a "gain of function" mechanism as oncogenes; if during translocation the imprinted gene loses the "imprinting sequence" that inhibited its expression, the genes become activated.…”
mentioning
confidence: 88%